1992
DOI: 10.1091/mbc.3.11.1279
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the domains in cyclin A required for binding to, and activation of, p34cdc2 and p32cdk2 protein kinase subunits.

Abstract: The binding of cyclin A to p34cdc2 and p32cdk2 and the protein kinase activity of the complexes has been measured by cell-free translation of the corresponding mRNA in extracts of frog eggs, followed by immunoprecipitation. A variety of mutant cyclin A molecules have been constructed and tested in this assay. Small deletions and point mutations of highly conserved residues in the 100-residue "cyclin box" abolish binding and activation of both p34cdc2 and p32cdk2. By contrast, large deletions at the N-terminus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
1
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 70 publications
(76 reference statements)
8
157
1
3
Order By: Relevance
“…2). Second, a fusion protein between protein A and a deletion mutant of cyclin A (Acc18), which is unable to bind to and activate cdc2 kinase (Kobayashi et al, 1992), was compared with the wild-type fusion protein. Acc18 cyclin A failed to block endocytic vesicle fusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). Second, a fusion protein between protein A and a deletion mutant of cyclin A (Acc18), which is unable to bind to and activate cdc2 kinase (Kobayashi et al, 1992), was compared with the wild-type fusion protein. Acc18 cyclin A failed to block endocytic vesicle fusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Or alternatively, CSF arrest can be determined through the detection of Cyclin B (data not shown). The presence of low calcium concentration activates Cyclin B destruction driving mitosis exit Kobayashi et al, 1992;Lorca et al, 1993). It is worth reiterating at this point that CSF arrested extracts are meiotic (meiosis II), but enable relevant insights by mimicking mitosis.…”
Section: Atm and Atr Activation In Mitotic Xenopus Egg Extractsmentioning
confidence: 99%
“…Since A17 proved to be the most reliable reagent for detecting and immunoprecipitating p34 cdc2 (Kobayashi et al 1992;Nebreda et al 1995;Goodger et al 1996), we decided to map the epitope it recognized. Preliminary investigation showed that it did not react with CDK2 from any species tested (data not shown), and that its reaction with chimeric Cdc2-CDK2 targets indicated that the epitope was in the C-terminal half of p34 cdc2 , but not beyond residue 228.…”
Section: Resultsmentioning
confidence: 99%